The value of contrast-enhanced ultrasonography in differential diagnosis of primary testicular germ cell tumors and non-germ cell tumors over 50 years old - Xue, Nianyu; Wang, Guoyao; Zhang, Shengmin; Lu, Yijun (Frontiers in Oncology, 2023)
Background Unlike young and middle-aged patients, seminoma is not common in patients with primary testicular tumors over the age of 50, so it cannot follow the general ideas and norms for diagnosing and treating testicular tumors, and its characteristics need to be considered separately. Methods The conventional ultrasonography and contrast-enhanced ultrasonography (CEUS) findings of primary testicular tumors in patients over 50 years old were retrospectively analyzed and compared with the pathological results to compare the diagnostic value of these two methods. Results Of the 13 primary testicular tumors, 8 were primary lymphomas. Conventional ultrasound of 13 cases of testicular tumors showed hypoechoic with rich blood flow, and it was difficult to identify the type accurately. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of conventional ultrasonography in diagnosing non-germ cell tumors (lymphoma and Leydig cell tumor) were 40.0%, 33.3%, 66.7%, 14.3%, and 38.5%, respectively. CEUS findings: 7 of 8 lymphomas showed uniform hyperenhancement. 2 cases of Leydig cell tumors showed uniform high enhancement. 2 cases of seminoma and 1 case of spermatocytic tumor showed heterogeneous enhancement, with necrosis in the interior. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy rate of non-germ cell tumor diagnosis according to the non-necrotic area of CEUS were 90.0%, 100.0%, 100.0%, 75.0% and 92.3%, respectively. Compared with conventional ultrasound, the difference was statistically significant (P=0.039). Conclusions Primary testicular tumors in patients over 50 years old are mainly lymphoma, and CEUS is significantly different between germ cell tumors and non-germ cell tumors. Compared with conventional ultrasound, CEUS can distinguish testicular germ cell tumors from non-germ cell tumors more accurately. Preoperative ultrasonography is significant for accurate diagnosis and can guide clinical treatment.